An Entropy Source based on the Bluetooth Received Signal Strength Indicator - Giron, Alexandre; Custódio, Ricardo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2020: Anais do XX Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2020)
The Bluetooth Low Energy (BLE) is one of the popular communication technologies employed in the Internet of Things (IoT) context. IoT devices need random numbers to feed their security mechanisms, where the generation of random numbers presupposes the existence of entropy sources. However, there are few entropy sources available, due to the limited hardware resources of those devices. Given this scenario, this paper presents a scalable approach for gathering entropy, called Bluerandom. The approach is based on the Received Signal Strength Indicator (RSSI) within Bluetooth communications. The results show that Bluerandom can be used as an alternative source of entropy, improving the robustness of the cryptographic mechanisms for the IoT context.